DIALOGUE BETWEEN WORLD RELIGIONS AND GLOBAL THEOLOGY: . - Kondrat, Kazimierz (Journal of Dharma, 2002)
Dialogue between great world religions (I mean Judaism, Christianity, Islam, Hinduism, Buddhism and Taoism) is nowadays inevitable. The growing possibility of direct communication with people of different world-views, beliefs, customs and practices, seems to be one of the main factors to impose the need of inter-religious and inter-cultural conversation on those who really want not only to understand adherents of different faiths and world-views but also to determine their own attitude towards them. One of the more remarkable and influential, but to some extent controversial, attempts in recent three decades at elaborating the idea of dialogue is that made by some modem British and American philosophers, theologians and comparative historians of religion.